Investigation of targets and anticancer mechanisms of covalently acting natural products by functional proteomics - Zhao, W. S.; Chen, K. F.; Liu, M.; Jia, X. L.; Huang, Y. Q.; Hao, B. B.; Tan, M. J.
Eriocalyxin B (EB), 17-hydroxy-jolkinolide B (HJB), parthenolide (PN), xanthatin (XT)and andrographolide (AG)are terpenoid natural products with a variety of promising antitumor activities, which commonly bear electrophilic groups (?,?-unsaturated carbonyl groups and/or epoxides)capable of covalently modifying protein cysteine residues. However, their direct targets and underlying molecular mechanisms are still largely unclear, which limits the development of these compounds. In this study, we integrated activity-based protein profiling (ABPP)and quantitative proteomics approach to systematically characterize the covalent targets of these natural products and their involved cellular pathways. We first demonstrated the anti-proliferation activities of these five compounds in triple-negative breast cancer cell MDA-MB-231. Tandem mass tag (TMT)-based quantitative proteomics showed all five compounds commonly affected the ubiquitin mediated proteolysis pathways. ABPP platform identified the preferentially modified targets of EB and PN, two natural products with high anti-proliferation activity. Biochemical experiments showed that PN inhibited the cell proliferation through targeting ubiquitin carboxyl-terminal hydrolase 10 (USP10). Together, this study uncovered the covalently modified targets of these natural products and potential molecular mechanisms of their antitumor activities.
Keywords: NATURAL PRODUCTS; PROTEOMICS; ABPP; ERIOCALYXIN B; PARTHENOLIDE